The Implementation of Mel-T Program in Improving Students' Speaking Performance at MAN 1 Polman - Sariana; Marliana, Rina; Uswatunnisa (Universitas Cokroaminoto Palopo, 2026)
Over the past nine years, students at MAN 1 Polman have shown low proficiency in English speaking and have not achieved recognition in English competitions. To address these issues, the school implemented the Mel-T program as a strategic initiative to enhance students’ English abilities, particularly in speaking. This study aimed to explore how the Mel-T program was implemented to improve students’ speaking performance, as well as to identify its benefits and the challenges faced by both members and the coach.This research employed a qualitative approach using a phenomenological method. The data were collected through observation, interviews, and documentation, then analyzed using NVivo 12 Plus software. The findings revealed that the Mel-T program was implemented systematically and effectively through three stages: opening, main, and closing activities. The opening phase involved greetings and motivational sessions, the main phase focused on various speaking practices, and the closing phase included evaluation and reflection. Data were gathered from three Mel-T meetings. In the first session, students participated in group discussions; the second focused on watching an English movie followed by a language game; and the third concluded with a talent show that showcased students’ speaking abilities. Interviews revealed several advantages of joining the program, such as increased confidence, improved speaking skills, better pronunciation, enriched vocabulary, enhanced debating skills, and higher participation in English competitions. However, despite these benefits, some students still faced challenges, including limited vocabulary, pronunciation difficulties, and a lack of confidence. Additional obstacles included poor grammar understanding and limited environmental support for English practice. From the coach’s perspective, the main challenges involved students’ shyness, fear of making mistakes, and difficulties maintaining active engagement. Overall, the Mel-T program proved to be a valuable platform for improving students’ speaking performance while also highlighting areas that require further attention and support.